The Mathematical Problem-solving Ability of Elementary Students Using Problem-based Learning Model with Open-Ended Approach (Universitas Negeri Semarang, 2019)
This study has a purpose of determining the effectiveness of problem-based learning models with open-ended approach on students' mathematical problem-solving abilities; the comparison of the effectiveness of problem-based learning with open-ended approach and discovery learning on students' mathematical problem-solving abilities; describe the students' mathematical problem-solving abilities. This type of research was a quantitative narrative with a true experimental design. Quantitative data collection was done using a test and interview. Based on the analysis and discussion, it can be concluded that the problem-based learning models with open-ended approach were effective in improving the students' mathematical problem-solving ability, it can be seen from the classical completeness of the experimental class which is more than 75%, the average of experimental class’s problem-solving ability was higher than the class with discovery learning, the students with high problem-solving ability were able to meet all the indicators of problem-solving, the students with moderate problem-solving ability were not able to write down the problem-solving steps, and the students with low problem-solving ability were still making a mistake in the calculation and drawing conclusion.